Automatyczne wspomaganie anonimizacji orzeczeń sądowych - Olszowski, Krzysztof; Rosłon, Dariusz (Kwartalnik Prawa Publicznego, 2012)
Public access to court rulings is crucial to the right of access to court and can help improve the quality of case law. Public opinion demands up-to-date and comprehensive legal information. It is not enough to publish the “most important” verdicts. Each one may be most important. It seems inevitable to allow access to all rulings. The rulings must be anonymized in order to protect private data. Manual stripping of sensitive information is a cumbersome and risky process. Automated assistance is necessary. A semi intelligent system GALL, developed for Administrative Courts, provides an effective and safe support. It analyses ruling texts searching for sensitive data e.g. names, addresses, amounts and suggests the safe abbreviations. The user can accept or edit the anonymized text. The assisted process is twice faster and significantly safer than manual anonymization.